2018
DOI: 10.1002/pen.25002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance of the novel PVDF ultrafiltration membranes blending with PVA modified SiO2 hydrophilic nanoparticles

Abstract: In this study, PVA‐SiO2 was synthesized by modifying silica (SiO2) with polyvinyl alcohol (PVA), then a novel polyvinylidene fluoride (PVDF) ultrafiltration (UF) membrane was prepared by incorporating the prepared PVA‐SiO2 into membrane matrix using the non‐solvent induced phase separation (NIPS) method. The effects of PVA‐SiO2 particle on the properties of the PVDF membrane were systematically studied by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT‐IR), surface pore size, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Poly­(vinylidene) fluoride (PVDF) is a well-established polymeric material to produce ultrafiltration (UF) and microfiltration (MF) membranes owing to its exceptional mechanical properties, chemical resistance, and thermal stability. However, despite its many advantages, the hydrophobicity of PVDF can induce severe membrane fouling, which is a main obstacle that limits its applications. Thanks to the compatibility of the PVDF matrix with amphiphilic copolymers, modifications of PVDF membranes by blending with other more hydrophilic components have been reported widely. The atom transfer radical polymerization (ATRP) method can be applied to enhance the properties of polymers by grafting chains with different characteristics, making the preparation of many new copolymers possible. Specifically, PVDF- graft -poly­(ethylene glycol) methyl ether methacrylate (PVDF- g -PEGMA) has been successfully synthesized and characterized. ,, Membranes with promising fouling resistance behavior were thus produced by blending this PVDF- g -PEGMA material with traditional PVDF …”
Section: Introductionmentioning
confidence: 99%
“…Poly­(vinylidene) fluoride (PVDF) is a well-established polymeric material to produce ultrafiltration (UF) and microfiltration (MF) membranes owing to its exceptional mechanical properties, chemical resistance, and thermal stability. However, despite its many advantages, the hydrophobicity of PVDF can induce severe membrane fouling, which is a main obstacle that limits its applications. Thanks to the compatibility of the PVDF matrix with amphiphilic copolymers, modifications of PVDF membranes by blending with other more hydrophilic components have been reported widely. The atom transfer radical polymerization (ATRP) method can be applied to enhance the properties of polymers by grafting chains with different characteristics, making the preparation of many new copolymers possible. Specifically, PVDF- graft -poly­(ethylene glycol) methyl ether methacrylate (PVDF- g -PEGMA) has been successfully synthesized and characterized. ,, Membranes with promising fouling resistance behavior were thus produced by blending this PVDF- g -PEGMA material with traditional PVDF …”
Section: Introductionmentioning
confidence: 99%
“…Initially, core SiO 2 nanoparticles (NPs) were simply synthesized through the well-known Sto ¨ber method [51][52][53] in ethanol media with tetraethyl orthosilicate (TEOS) and catalyzed by ammonia to make the hydrophilic surface of synthesized NPs. [54][55][56] FE-SEM images of synthesized SiO 2 NPs clearly demonstrated quite uniform and spherical particles distribution with a narrow average size of about 100 (AE5) nm, which could also be tuned by adjusting the concentration of TEOS. SiO 2 NPs were re-dispersed in ethanol using ultrasonication and coated onto the Ni-mesh via a dip-coating process.…”
Section: Resultsmentioning
confidence: 99%
“…Now a day's applications extended to separation process, nanoporous silica provide inner channels for water molecules and enhance water flux also offer attractive possibilities for the preparation of ultrafiltration nanocomposite membrane. demonstrated that hydrophilicity, water flux and rejection of bovine serum albumin increased due to hydroxyl groups of polyvinyl alcohol and silica particles [56].…”
Section: Silicon Oxide Based Nanocomposite Membranesmentioning
confidence: 99%